2013
DOI: 10.1159/000346561
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal Contrast-Enhanced Ultrasonography, Transrectal Ultrasonography and Retrograde Cystography for the Detection of Vesicourethral Anastomosis Leakage after Radical Retropubic Prostatectomy: A Prospective Comparative Evaluation

Abstract: Objectives: To evaluate the diagnostic accuracy of cystography (CG), transrectal ultrasonography (TRUS) and transrectal contrast-enhanced ultrasonography (CEUS) for the detection of vesicourethral extravasation (VE) after radical retropubic prostatectomy (RRP). Patients and Methods: In 80 consecutive patients who underwent RRP, the strength of the vesicourethral anastomosis (VUA) was assessed by CG, TRUS and transrectal CEUS. The investigation started with a conventional CG evaluated by an experienced uroradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…In another study without an ultrasound contrast agent, Eggert et al [3] also reported good agreement between the transrectal ultrasound and cystography in a cohort of 100 men (21 leakages detected using cystography and 23 leakages detected using the transrectal ultrasound). Further, Cantiello et al [4] used an ultrasound contrast agent and reported detection rates very similar to cystography rates for anastomotic leakage using transrectal ultrasound. In this study of 80 men, 26 anastomotic leaks were detected by cystography, of which 24 were detected by transrectal ultrasound without contrast and 25 by transrectal ultrasound using a contrast.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In another study without an ultrasound contrast agent, Eggert et al [3] also reported good agreement between the transrectal ultrasound and cystography in a cohort of 100 men (21 leakages detected using cystography and 23 leakages detected using the transrectal ultrasound). Further, Cantiello et al [4] used an ultrasound contrast agent and reported detection rates very similar to cystography rates for anastomotic leakage using transrectal ultrasound. In this study of 80 men, 26 anastomotic leaks were detected by cystography, of which 24 were detected by transrectal ultrasound without contrast and 25 by transrectal ultrasound using a contrast.…”
Section: Resultsmentioning
confidence: 90%
“…Seven articles compared cystography using pelvic Xrays versus ultrasound-guided assessment, and two compared cystography with computerized tomography (CT; Table 1). For ultrasound-guided assessments, three transducer locations, including transrectal (n = 4, [2][3][4][5]), transabdominal (n = 2, [6,7]), and transperineal (n = 1, [8]) positions were used, and saline was applied through the transurethral catheter with or without an ultrasound contrast agent.…”
Section: Resultsmentioning
confidence: 99%
“…и M. Schenck и соавт. не выявили статистически значимой разницы между динамическим трансректальным ультразвуковым исследованием и ретроградной цистографией для оценки несостоятельности УВА [3,4]. В проспективном исследовании O.K.…”
Section: Discussionunclassified
“…All patients underwent an ultrasound control of the anastomosis on the seventh postoperative day, as we usually do (9, 10).…”
Section: Methodsmentioning
confidence: 99%